Macrophage subpopulations and macrophage-derived cytokines in sputum of atopic and nonatopic asthmatic subjects and atopic and normal control subjects - Zeibecoglou, Kyriaki; Ying, Sun; Meng, Qiu; Poulter, Leonard W.; Robinson, Douglas S.; Kay, A.Barry (Journal of allergy and clinical immunology, 2000)
Background: Previous studies have shown a prominent macrophage signal in the bronchial mucosa from nonatopic (intrinsic) compared with atopic (extrinsic) asthmatic subjects. This observation might have represented an expansion of a proinflammatory macrophage population or a homeostatic mechanism to decrease TH2-type inflammation. Objective: The aim of the study was to investigate the numbers of macrophages and macrophage subpopulations and the expression of IL-10 and IL-12 in sputum from asthmatic and control subjects. Methods: Eight atopic asthmatic (AA) subjects, 10 nonatopic asthmatic (NAA) subjects, 6 atopic control (AC) subjects, and 7 normal control (NC) subjects underwent sputum induction. Macrophages were enumerated by using Romanowsky stain and immunocytochemistry (CD68). RFD1 (interdigitating cell marker) and RFD7 (mature phagocyte marker) mAbs were used for immunocytochemical phenotyping, whereas IL-10 and IL-12 messenger (m)RNA was examined with in situ hybridization by using 35S-labeled riboprobes. The phenotype of cells expressing IL-10 or IL-12 mRNA was examined by simultaneous in situ hybridization and immunostaining. Results: No differences in the numbers of CD68+ macrophages and RFD1+, RFD7+, and RFD1+/RFD7+ subpopulations were found between AA, NAA, AC, and NC subjects. However, the numbers of IL-10 and IL-12 mRNA+ cells were increased in AA subjects compared with NAA, AC, and NC subjects (P < .05). No other differences were found among the groups. Most of the IL-10 and IL-12 mRNA+ cells in sputum from asthmatic subjects were macrophages (>80%), with less than 10% of mRNA colocalizing to epithelial cells. Conclusions: Sputum macrophage numbers, unlike tissue macrophages, as previously reported, were not elevated in NAA subjects. Increased IL-10 and IL-12 expression in atopic asthma may indicate the existence of a homeostatic mechanism to decrease lung inflammation. The lack of such cytokines in intrinsic asthma may predispose to bronchial inflammation in these subjects. (J Allergy Clin Immunol 2000;106:697-704.)